Definition of remission and relapse in polymyalgia rheumatica: data from a literature search compared with a Delphi-based expert consensus. Issue 3 (19th November 2010) - Dejaco, Christian; Duftner, Christina; Cimmino, Marco A; Dasgupta, Bhaskar; Salvarani, Carlo; Crowson, Cynthia S; Maradit-Kremers, Hilal; Hutchings, Andrew; Matteson, Eric L; Schirmer, Michael
Abstract : Objective: To compare current definitions of remission and relapse in polymyalgia rheumatica (PMR) with items resulting from a Delphi-based expert consensus. Methods: Relevant studies including definitions of PMR remission and relapse were identified by literature search in PubMed. The questionnaire used for the Delphi survey included clinical (n=33), laboratory (n=54) and imaging (n=7) parameters retrieved from a literature search. Each item was assessed for importance and availability/practicability, and limits were considered for metric parameters. Consensus was defined by an agreement rate of ≥80%. Results: Out of 6031 articles screened, definitions of PMR remission and relapse were available in 18 and 34 studies, respectively. Parameters used to define remission and/or relapse included history and clinical assessment of pain and synovitis, constitutional symptoms, morning stiffness (MS), physician's global assessment, headache, erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), blood count, fibrinogen and/or corticosteroid therapy. In the Delphi exercise a consensus was obtained on the following parameters deemed essential for definitions of remission and relapse: patient's pain assessment, MS, ESR, CRP, shoulder and hip pain on clinical examination, limitation of upper limb elevation, and assessment of corticosteroid dose required to control symptoms. Conclusions: Assessment of patient's pain, MS, ESR, CRP, shoulder pain/limitation on clinical examination and corticosteroid dose are considered to be important in current available definitions of PMR remission and relapse and the present expert consensus. The high relevance of clinical assessment of hips was unique to this study and may improve specificity and sensitivity of definitions for remission and relapse in PMR.